Karakteristik Cendawan Mikoriza Arbuskula (CMA) pada Beberapa Rhizosfer Tanaman Perkebunan - Indra Yuliyanto; Bambang Utoyo; Dewi Riniarti (Jurnal Agro Industri Perkebunan, 2016)
The development of Mycorrhizal Arbuscular Fungi (MAF) in general is influenced by the conditions of the rhizosphere and fungi spores. Rhizosphere conditions are conditions around the roots such as temperature, pH, and root exudates. While the condition is a fungal spore dormancy and maturity spores. The aim of this study was to determine the amount of FMA on some plantation crops rhizosphere, to determine the type of crop rhizosphere FMA on some plantations, as well as to determine the dominance of FMA on some plantation crops rhizosphere. The experiment was conducted at the Laboratory Analysis State Polytechnic of Lampung. Month trial period from December 2014 to July 2015. The method used in this study is a description of the method by observation. Based on research results and observations of mycorrhizal spores in the rhizosphere of plants cocoa, rubber, coffee, and palm oil was found that on average the highest number of spores found in oil palm plantations (2.4 spores), while the lowest number of spores present in the rubber plantations (1 spore ). Type spores on all plantation crops rhizosphere dominated by species Glomus with different types (10 types). Glomus Type 2 dominates on all plantation crops rhizosphere.Keywords: estate crop, mycorrhizae, rhizospherePermalink:Â http://jurnal.polinela.ac.id/index.php/AIP/article/view/51